Detection of Ground in Point-clouds Generated from Stereo-pair Images (Informatica, 2015)
This paper proposes a new approach for constructing digital terrain models (DTM) from the point-cloudsgenerated from airborne stereo-pair images. The method uses data decomposition based on the differentialattribute profiles and -mapping for the extraction of the most-contrasted connected-components. Theirfiltering is achieved based on multicriterion threshold function. The method is evaluated by comparing theoutput DTM with the reference Light Detection and Ranging data (LiDAR).